New climate regime restructures the ecology of Canada’s Northern Great Lakes - Kathleen M. Rühland; Neal Michelutti; Marlene S. Evans; Kimberly L. Howland; John P. Smol (Proceedings of the National Academy of Sciences, 2026)
Great Bear Lake (GBL), Great Slave Lake (GSL), and Lake Hazen in northern Canada have recently experienced a shift in fundamental aquatic ecosystem processes associated with accelerated Arctic warming. Multiple high-resolution, 210 Pb-dated sediment records (GBL: Smith, Keith, McVicar arms, GSL: West Basin, Lake Hazen: Blister, Main sites) registered remarkably similar restructuring of algal community composition over the past few decades in all lakes. A rapid proliferation of small euplanktonic diatoms at the turn of the 21st century displaced benthic (GBL, Lake Hazen) and large filamentous (GSL) taxa that dominated the diatom assemblages since the mid-to-late 1800s. An increase in the number of ice-free days, a rise in regional air temperature, and a decline in wind speed primed the lakes for new physical and thermal regimes that facilitated a shift to greater whole lake primary production and favored small obligate planktonic diatoms. Historical records from surveys undertaken on the lakes between the 1940s and 1970s substantiated our paleolimnological findings that these lakes were relatively stable limnologically since at least the past century and have only recently transitioned to new thermal states. As primary producers fuel the entire food web, this rapid algal community restructuring serves as a cautionary signal of major ecosystem changes. The characteristic thermal inertia and resilience of Canada’s “Northern Great Lakes” is rapidly eroding, with implications for native fish populations that Indigenous and other northern communities rely on.